PROCESS PRODUCTION OF FLUTED ROLL ON ROLL MILLS MACHINERY - Abdul Muchlis; Akbar Harist Alfatritsy (Asosiasi Dosen Muda Indonesia, 2022)
Wheat as raw material for flour, is milled using a Fluted Roll in a Roll Mill machine. Fluted Rolls are made through a machining process that aims to obtain the desired shape, size, and level of surface roughness. This study aims to determine the material contained in Fluted Rolls and the process of making Fluted Rolls through machining processes, such as milling and scraping, as well as welding processes. The results of this study conclude the fluted roll machining process using steel medium carbon, namely JIS S45C and high alloy steel (High Alloy Steel) namely AISI 410, the milling process uses a vertical milling machine, and the scrap machining process uses a CNC (Computer Numerical Control) scrap machine in making flutes on the fluted roll surface. In the milling process using a blade diameter of 20 mm and a main spindle speed of 600 rpm, the machine's cutting speed is 37.68 mm/minute. Welding process on fluted roll aims to connect the milled shaft with the roller mill using TIG (Tungsten Inert Gas). In the scrap machining process, the feeding speed used is 9000 mm/minute and the chisel return speed to point 0 is 27132 mm/minute, resulting in a one-time feeding time of 14.24 seconds. The total time for working on fluted rolls with B3f specifications is the total flute 550, diameter 250 mm, length 1250 mm, and the slope of the flutes that form a spiral is 10% for 2 hours 10 minutes 53 seconds.